Testate Amoebae of Peru: filling the gap in the Neotropics - Bobrov, Anatoly (2019)
Testate amoebae diversity from 28 surface (0-3 cm depth) soil samples found near Cuzco (6 samples), in Machu Piсchu (17 samples), in Aguas Calientes (5 samples), and one bottom sediment sample from the Lake Titicaca near the Puno collected during March of 2016 were analyzed. The 144 testate amoebae species and infra-specific taxa belonging to 27 genera were identified. Nineteen amoebae have not been identified to species levelnd likely represent new taxa. Species richness varied from one to 54 taxa per sample. The highest diversity was found in rainforests followed by those in meadows and agave habitats. The only bottom sample from Lake Titicaca has yielded two hydrobiont species from the genus Difflugia. In the course of the study, several rare species with limited geographical distribution were observed, namely Centropyxis castaneus, C. compressa, C. deflandriana, C. latideflandriana, C. cf. ohridensis, C. cf. ovoides, C. cf. pannosus, C. stenodeflandriana, Cyclopyxis plana, C. profundistoma, Apodera vas, Argynnia retorta, A. spicata, Certesella certesi, Trachelcorythion pulchellum. Our study fills a geographical gap in the distribution of some flagship species with restricted geographic distribution, e.g. Apodera vas and Certesella certesi in Peru. The results illustrate the continuity of expansion species along the Pacific coast.